Low Serum Asprosin Levels in Fibromyalgia Syndrome: Insights from a Cross-Sectional Study - Uslu, Muhammed Fuad; Uslu, Emine Yildirim; Yildiz, Sevler; Tabara, Muhammed Fatih (Mdpi, 2025)
Background and Objectives: This study aimed to evaluate serum asprosin levels in female patients with fibromyalgia syndrome (FM), investigate their associations with clinical parameters such as disease severity, anxiety, and depression, and evaluate the potential of serum asprosin levels as a biomarker for fibromyalgia diagnosis. Materials and Methods: A total of 80 participants were included in the study, 40 women aged 18-60 years who were diagnosed with FM according to the American College of Rheumatology (ACR) 2016 criteria and 40 healthy women with similar sociodemographic characteristics to the patient group. All participants were measured for hemograms, biochemistry tests, and serum asprosin levels. Additionally, the Fibromyalgia Impact Questionnaire (FIQ), Beck Anxiety Inventory (BAI), and Beck Depression Inventory (BDI) were administered to the patient group. Results: The median asprosin level in the case group was 15.01 (SD = 10.08-31.42), while in the control group it was 31.03 (SD = 25.14-35.7). The asprosin levels in the case group were significantly lower than those in the control group (p = 0.001). In contrast, AST, vitamin B12, and folic acid levels were significantly higher in the case group than in the control group. When all participants were evaluated, asprosin levels showed a significant positive correlation with systolic arterial blood pressure (Rho = 0.337, p = 0.002) and diastolic arterial blood pressure (Rho = 0.238, p = 0.033). A cut-off value of 17.72 ng/mL for asprosin levels in the diagnosis of fibromyalgia demonstrated a sensitivity of 60% and a specificity of 90%. Conclusions: Low asprosin levels may serve as a potential biomarker for the diagnosis of fibromyalgia in women.
Keywords: fibromyalgia; asprosin; anxiety; depression